Influences reverberation time to human activities: method to measure reverberation time for different mosque structure - Mohd Faiz, Abd Halim; Mohd Noor Arib, Md Rejab; Fauziah, Mat (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.